EVALUASI PARAMETER HEMATOLOGI PADA PASIEN TUBERKULOSIS PARU DI KOTA BANDAR LAMPUNG - Filia Yuniza; Sri Nuraini; Bayu Putra Danan Jaya (Politeknik Kesehatan Kemenkes Bengkulu, 2022)
Correct early diagnosis is crucial to control pulmonary tuberculosis infection (TB). This study aims to evaluate hematological parameters in tuberculosis patients to obtain parameters that can support the initial diagnosis of tuberculosis. A total of 36 patients diagnosed with TB based on rapid molecular tests and sputum smears compared the results of their hematological examination with 28 healthy volunteers according to age and sex. The routine blood tests examined were Hb, Ht, erythrocyte index, erythrocytes, leukocytes, and platelets count. TB patients had significantly lower Hb, Ht, MCV, and MCH mean levels compared to the healthy volunteer group (p<0.05). TB patients also had a significantly higher mean leukocyte and platelets count than the healthy volunteer (p<0.001). Conclusion: Hb, Ht, MCV, MCH, and leukocytosis decrease can be used as supporting diagnostic for the initial diagnosis of TB.